Demographically-adjusted norms for the Grooved Pegboard and Finger Tapping tests in Spanish-speaking adults: Results from the Neuropsychological Norms for the U.S.-Mexico Border Region in Spanish (NP-NUMBRS) Project. Issue 2 (6th February 2021) - Heaton, Anne; Gooding, Amanda; Cherner, Mariana; Umlauf, Anya; Franklin, Donald R.; Rivera Mindt, Monica; Suárez, Paola; Artiola i Fortuni, Lidia; Heaton, Robert K.; Marquine, María J.
Abstract: Objective: We developed demographically-corrected norms for Spanish-speakers from the U.S.-Mexico border regions of California and Arizona on two tests of motor skills - the Grooved Pegboard Test (Pegboard) and Finger Tapping Test (Tapping) - as part of a larger normative effort. Method: Participants were native Spanish-speakers from the Neuropsychological Norms for the U.S.-Mexico Border Region in Spanish (NP-NUMBRS) Project (Pegboard: N  = 254; Tapping: N  = 183; age: 19–60 years; education: 0–20 years; 59% women). We examined the association of demographics (age, education and gender) with raw scores. Raw test scores were then converted to demographically-corrected T-scores via fractional polynomial equations. We also examined rates of impairment (T-score < 40) based on the current norms and on previously published norms for English-speaking non-Hispanic Whites and Blacks. Results: Having more years of education was associated with better raw test score performance on both tests ( p  < .001), and increased age was associated with worse performance on Pegboard ( p  < .001). Men outperformed women on Tapping, and older age was associated with lower raw scores in men only on the Tapping non-dominant hand trial ( p  = .02). The normed T-scores were confirmed to be normally distributed and free from demographic influences, and resulted in expected rates of impairment. Applying existing norms for English-speaking non-Hispanic Whites and Blacks to the raw scores of Spanish-speakers generally yielded lower than expected impairment rates (2–13%), with one exception: non-dominant Pegboard, for which non-Hispanic White norms overestimated impairment (23%). Conclusions: Present findings underscore the importance of appropriate, population-specific normative data, even for tests of motor ability.